Relationship between 800-m running performance and aerobic and anaerobic energy metabolism capacities in well-trained middle-distance runners - Tanji, F.; Tsuji, T.; Shimazu, W.; Nabekura, Y. (International Journal of Sport & Health Science, 2018)
The aim of this study was to elucidate the relationship between the 800-m running performance and aerobic and anaerobic energy metabolism capacities in well-trained middle-distance runners. This study was conducted on 12 male middle-distance runners (age 19.7 ± 0.9 years, height 170.0 ± 4.6 cm, body weight 58.9 ± 3.0 kg, body fat 7.8% ± 1.2%, 800-m season best time 1'53.2 ± 2.2 and equivalent to an average velocity of 25.4 ± 0.4 km·h-1 over 800 m). Participants underwent three running tests on a treadmill to assess aerobic (maximal oxygen uptake [VO2max], lactate threshold intensity [LTI], running economy [RE]) and anaerobic (maximal accumulated oxygen deficit [MAOD] and maximal accumulation blood lactate concentration [DetabLa]) energy metabolism capacities. The results demonstrated a significantly negative relationship between the 800-m running velocity and RE and MAOD (r = -0.78 and -0.72, respectively), but not with VO2max, LTI, and DeltabLa (r = -0.16, -0.17 and 0.11, respectively). Furthermore, this study demonstrated that >70% of the 800-m running velocity could be explained by RE, LTI, and DeltabLa. These results suggest that RE affects the 800-m running performance in well-trained runners.